Geospatial assessment of household water, sanitation and hygiene conditions and associated factors in Nigeria: A causal relationship model - Jacob W. Mobolaji; Akinola Shola Akinwumiju (PLoS ONE, 2025)
Lack of adequate access to safe water, sanitation, and hygiene (WASH) has contributed to increased under-five mortality and morbidity of school-age children in low- and middle-income countries. Despite the global and national intervention programs, access to safe WASH remains a critical challenge in Nigeria. This study employed spatial and non-spatial statistics to establish causal relationships between WASH conditions and household factors in Nigeria. Results show that a large proportion of Nigerian households were still associated with unimproved hygiene (88%), sanitation (47%) and water (25%). Wealth status, literacy level and residency type exhibit significant causal relationships with households’ water sources (α = 0.000). Wealth status and the gender of household head exhibit significant causal relationships with sanitation condition (α = 0.000) and hygiene condition (α = 0.004 and α = 0.345, respectively). However, the computed parameter Degree of Dependence (DoD_j) shows that the choice of water sources mostly depends on residency type (DoD_j = 0.998) compared with the level of education and wealth status (DoD_j = 0.535 and 0.485, respectively). Statistical indices show that the implemented regression models are reliable (with models’ DoD of 0.714–0.996, Adjusted R2 of 0.184–0.762 and Akaike Information Criterion (AICc) of 68–103). The study concludes that a high risk of unimproved WASH is associated with rural residence, which is usually characterised by a low level of education, poverty and large household size. It further concludes that the high prevalence of unimproved hygiene, irrespective of the household wealth status and educational level, suggests the need for proper health and hygiene education. This study suggests the need for a more focused policy action towards empowering rural and vulnerable households in Nigeria with relevant preventive environmental and health information and appropriate social support for the communities.